Changes in upper body concentric mean power output resulting from complex training emphasizing concentric muscle actions - Baker, D. (Journal of Australian Strength and Conditioning, 2012)
Contrasting resistance complex (CRC) training is the alternating of sets of heavier and lighter resistances in an effort to evoke an acute increase in power output while lifting the lighter resistance. The effectiveness of CRC has been well established in elite athletes when researchers utilize an optimal manipulation of training variables but equivocal for other studies that have used a very heavy resistance to "stimulate" the neuro-muscular system. It was theorized that very heavy resistances could conceivably fatigue the processes associated with the stretch-shorten cycle (SSC). The purpose of this study was to determine the effects of CRC when utilizing concentric-emphasis exercises that negate the role or effect that the SSC may have upon power output. Eleven professional rugby league players volunteered to perform a CRC consisting of two sets of three repetitions each of paused concentric-only bench throws with 60 kg (CO BTP60) alternated with paused concentric-emphasis narrow grip bench presses to a board device placed upon their sternum. The board device consisted of 2 x 5 cm wide boards nailed together such that the barbell rested upon this 10 cm thick board device rather than impacting the chest at the bottom of the movement. Mean concentric power output during CO BTP60 increased by about 3% as a result of the intervention of the heavier paused board BP. The results of this study demonstrate that the CRC is enhancing performance without use of the normal SSC action. Such a result is likely to be caused by an increase in neural drive associated with the CRC.